2021
DOI: 10.1007/s42241-021-0097-6
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of transient cavitation control on a hydrofoil using hemispherical vortex generators

Abstract: Unsteady cavitation causes noise, damage, and performance decline in the marine engineering and fluid machinery systems. Therefore, finding a method to control the cavitation and its destructive effects is important for the industrial applications. In this work, we proposed a passive method to control the unsteady behavior of transient cavitation at the medium Reynolds number. For this aim, we performed an experimental study using a high-speed camera to analyze the effects of hemispherical vortex generators (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Furthermore, they explain the effects of flow vorticity, pressure variation rate, bubble inertia and surface tension effects on the cavity dynamics. Kadivar et al [22,23] investigated the unsteady cavitation dynamics and surge cavitation occurring over both a hydrofoil and a semicircular flat plate. They concluded that the evolution of the sheet cavity to a cloud cavity diverges from the cavity structure dynamics within the cloud cavitating regime.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they explain the effects of flow vorticity, pressure variation rate, bubble inertia and surface tension effects on the cavity dynamics. Kadivar et al [22,23] investigated the unsteady cavitation dynamics and surge cavitation occurring over both a hydrofoil and a semicircular flat plate. They concluded that the evolution of the sheet cavity to a cloud cavity diverges from the cavity structure dynamics within the cloud cavitating regime.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic cavitation is often a harmful phenomenon in hydraulic engineering systems and marine applications that usually occurs on propeller blades, ship rudders and moving parts of hydraulic systems. It causes such undesirable effects as material erosion, high vibrational loads, increased noise and overall reduction of hydrodynamic performance (e.g., [54] , [19] , [27] , [51] , [36] , [37] , [56] . It is well known [21] that cavitation is initiated on immersible bodies in the flow regions where pressure locally falls below the one of saturated vapor of the surrounding liquid at a constant temperature, which can, for example, occur because of an increase in the flow velocity, a sudden change in the duct geometry, the passage of an acoustic wave during the half-periods of its expansion (ultrasound cavitation), etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the technique may not provide information on the quantity of vapor within the orifice. Kadivar et al [25,26] studied the effects of the pressure fluctuations in the cavitation surge regime around a two dimensional hydrofoil and a flat plate with semi-circular leading edge. They presented that the cavitation dynamics on the hydrofoil was driven mainly by the re-entrant jet in the cloud cavitation regime.…”
Section: Introductionmentioning
confidence: 99%